Late harvesting enhances granulation incidence in ‘Khao Yai’ pummelo (Citrus maxima (Burm.) Merr.) fruit - Sorot Thamarat,; Lop Phavaphutanon, (Agriculture and Natural Resources, 2021)
Granulation is an unfavorable characteristic found in citrus fruit including pummelo due to the juice sacs becoming hard, dry and tasteless, leading to poor fruit quality. The degree of granulation and fruit quality were compared of ‘Khao Yai’ pummelo harvested at three different stages: 1) early-harvest (1 mth before the optimum harvest for local market), 2) optimum-harvest and 3) late-harvest (1 mth after the optimum harvest for local market) in two consecutive crops (January and April) from the same set of trees. Granulation was detected in most fruit (84–100%) from all three harvesting stages. The degree of granulation was relatively low with less variation (0–38.8%) in fruits of early- and optimum-harvests and it increased significantly with more variation (1.9–81.7%) in late-harvest fruits. A similar trend was observed in both the January and April crops. The N, K, Mg and Na concentrations in the juice sac tissues were not significantly different among fruits with various degree of granulation. The Ca concentration (0.06–0.95%) in the juice sac tissues increased significantly with an increased degree of granulation in the April crop but not in the January crop within the range 0.08–0.20%. The degree of granulation tended to increase with increased fruit height, fruit circumference and fruit weight. Fruits from the April crop had higher total soluble solids (TSS) and lower titratable acidity (TA) than those from January crop. Normal juice sacs of fruits with different degrees of granulation had a relatively stable TSS (approximately 11°Brix) while the TA decreased with the progression of harvesting stages.